2014
DOI: 10.1111/1468-0106.12061
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Exposure of Sectoral Returns and Volatilities: Further Evidence From Japanese Industrial Sectors

Abstract: In this paper we argue that the commonly employed exposure coefficient/beta is inadequate to capture the entire impact of exchange rate changes on firms' future operating cash flows. Instead, we employ the bivariate GJR-GARCH-M models to investigate four aspects of exchange rate exposure, including sensitivity of stock returns to exchange rate changes, sensitivity of stock returns to the volatility of exchange rate changes, sensitivity of conditional variance of returns to exchange rate volatility, and the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The domestically reported return is exposed to the currency risk. To correct the biased estimates of the market beta, we take account of the foreign exchange risk and follow Jensen (1968Jensen ( , 1969; Lim (2005) and Jayasinghe et al (2014aJayasinghe et al ( , 2014b to specify the currency-adjusted international CAPM model as follows:…”
Section: Methodology and The Modelmentioning
confidence: 99%
“…The domestically reported return is exposed to the currency risk. To correct the biased estimates of the market beta, we take account of the foreign exchange risk and follow Jensen (1968Jensen ( , 1969; Lim (2005) and Jayasinghe et al (2014aJayasinghe et al ( , 2014b to specify the currency-adjusted international CAPM model as follows:…”
Section: Methodology and The Modelmentioning
confidence: 99%
“…Exchange Rate Exposure Initially, French et al, 1987;Campbell and Hentschel (1992) stated that there is a positive trade-off of risk and return, but researchers like Nelson's (1991) andGlosten's et al (1993) found contradicting evidence against it and showed outcomes that were different concerning GARCH bivariate model, where the risk associated with the stock return of market portfolio showed that the relationship between individual portfolio returns and the expected returns on portfolio altogether divergent. Recent evidence published on the subject by Jayasinghe et al (2014) reported and examined volatility associated risk that had captured the exchange rate exposure of sectorwise returns by testing the model to investigate four aspects of exchange rate exposure as stock return sensitivity to exchange rate volatility, stock return sensitivity to change in exchange rate exposure, stock return variance sensitivity to exchange rate volatility, and stock return dynamic correlation to exchange rate change and reported that the depreciation of Yen caused sectoral returns volatility to increase which depicted correlation of exchange rate changes and sectoral returns. Likewise, Bessler and Kurmann (2014) investigated that the assessment capital market for banking sector risk factors in the UK and the US during 1990-2011 by focusing on bank stock return in one or more-factor framework and identified multi-dimensional and time-varying bank risk exposures well integrated into the bank stock returns.…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%
“…Beside, PSSR and FSSR series does not have unit root problem, and these series are stationary at level, I (o), the p-values of the models resulted in very weak p-values as shown in table 5. The results of the study have been compared with the literature, and according to Jayasinghe et al (2014), the volatility associated risk did capture the exchange rate exposure of sector-wise returns and its impact on the firm's future operating cash flows was unprecedented. Therefore, in this study, the stock returns sensitivity to exchange rate volatility by using the petroleum and food industry sectors financial data.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations